An interface-based detailed micro-model for the failure simulation of masonry structures. (December 2022) - Gaetano, Daniele; Greco, Fabrizio; Leonetti, Lorenzo; Lonetti, Paolo; Pascuzzo, Arturo; Ronchei, Camilla
Highlights: A new micro-model is proposed to reproduce crack growth phenomena in masonry. The proposed model adopts a diffuse cohesive interface modeling strategy. A novel cohesive-frictional model is used for reproducing shear/compression status. A proper strategy to avoid non-uniqueness issues in numerical solutions is adopted. Simulations of direct tensile and shear tests on masonry couplets are performed. Abstract: This work presents a novel FE-based detailed micro-model approach, referred to as Discontinuous Detailed Micro-Model (DDMM), for the nonlinear analysis of masonry structures subjected to in-plane loading conditions. According to this DDMM, material nonlinearities caused by fracture phenomena at mortar joints are reproduced by means of zero-thickness interface elements placed between all brick/mortar and mortar/mortar interfaces comprised into the volumetric finite element mesh. In particular, the model adopts a novel cohesive-frictional interface model for reproducing the inelastic response under combined shear/compression stresses. The work provides a comprehensive investigation on the well-known nonuniqueness issues usually experienced in similar approaches, providing an effective numerical stabilization strategy. The proposed approach is validated through comparisons with experimental data available in technical literature, involving both tensile and combined shear/compression tests on brick masonry couplets. The results denote that the proposed approach ensures reliable predictions of the failure behavior of masonry structures.